Cellular Mechanisms of Sinus Node Dysfunction in Carriers of the SCN5A-E161K Mutation and Role of the H558R Polymorphism - Wilders, Ronald (Frontiers in Physiology, 2018)
Background: Carriers of the E161K mutation in the SCN5A gene, encoding the NaV1.5 pore-forming α-subunit of the ion channel carrying the fast sodium current (INa), show sinus bradycardia and occasional exit block. Voltage clamp experiments in mammalian expression systems revealed a mutation-induced 2.5 to 4-fold reduction in INa peak current density as well as a +19-mV shift and reduced steepness of the steady-state activation curve. The highly common H558R polymorphism in NaV1.5 limits this shift to +13 mV, but also introduces a −10-mV shift in steady-state inactivation. Aim: We assessed the cellular mechanism by which the E161K mutation causes sinus node dysfunction in heterozygous mutation carriers as well as the potential role of the H558R polymorphism. Methods: We incorporated the mutation-induced changes in INa into the Fabbri-Severi model of a single human sinoatrial node cell and the Maleckar et al. human atrial cell model, and carried out simulations under control conditions and over a wide range of acetylcholine levels. Results: In absence of the H558R polymorphism, the E161K mutation increased the basic cycle length of the sinoatrial node cell from 813 to 866 ms. In the simulated presence of 10 and 25 nM acetylcholine, basic cycle length increased from 1027 to 1131 and from 1448 to 1795 ms, respectively. The increase in cycle length was the result of a significant slowing of diastolic depolarization. The mutation-induced reduction in INa window current had reduced the contribution of the mutant component of INa to the net membrane current during diastolic depolarization to effectively zero. Highly similar results were obtained in presence of the H558R polymorphism. Atrial excitability was reduced, both in absence and presence of the H558R polymorphism, as reflected by an increase in threshold stimulus current and a concomitant decrease in capacitive current of the atrial cell. Conclusions: We conclude that the experimentally identified mutation-induced changes in INa can explain the clinically observed sinus bradycardia and potentially the occasional exit block. Furthermore, we conclude that the common H558R polymorphism does not significantly alter the effects of the E161K mutation and can thus not explain the reduced penetrance of the E161K mutation.